Study on Comparative Efficiencies in Vaccine Procurement Mechanisms - Bumpas, Janet (World Bank, Washington, DC, 2012)
Vaccinations are amongst the most cost-effective public health interventions. Vaccine procurement is a complex issue that interweaves the domains of public health, commodity security, ethics, and procurement. Its cross-disciplinary nature means that neither a straightforward analysis stemming from just one discipline nor a cookie-cutter application of World Bank procurement principles of economy, efficiency, equal opportunity, promoting domestic contracting and transparency will lead to an optimal solution. A more holistic approach is required. The World Bank has therefore historically considered vaccine procurement as 'special' and has allowed for exceptions from its guidelines for World Bank funded vaccine procurement. The study was designed to provide strong operational recommendations for issues such as efficiency, price, quality control, and logistics management. This study is intended mainly for internal purposes to facilitate discussions with Operations Policy and Country Service (OPCS) regarding refining the World Bank's position on procurement or supply of vaccine through United Nations Children's Fund (UNICEF).